PEMILIHAN KEPALA DAERAH LANGSUNG DI INDONESIA PRESPEKTIF AL-MAWARDI - Misalina Misalina; Elimartati Elimartati (Institut Agama Islam Negeri Batusangkar, 2022)
This study discusses the mechanism of direct regional head elections in Indonesia and the analysis of direct regional head elections in Indonesia from Al-Mawardi's perspective. Data collection techniques such as primary legal materials, secondary legal materials and tertiary legal materials, as well as data management so that they can answer problems. Based on the research that the author has done, it can be concluded that the mechanism for the first direct regional head election in Indonesia is based on Law Number 10 of 2016 concerning regional head elections which are carried out directly by using the stages of compiling the voter list, campaign stages for regional head requirements, polling vote and vote counting, appointment of regional heads. The second is an analysis of the implementation of direct regional head elections in Indonesia and according to al-Mawardi there are similarities and differences in the mechanism, requirements, authority of regional heads and stages of regional head elections.